Paradigma Etik Hukum dalam Konsep Tri Hablum sebagai Penguatan Regulasi Penanggulangan Kerusakan Lingkungan: Analisis Fikih Biah - Anwar, Nurul Mutmainna; Syukur, Muh.; Adnan, Ayu Zakinah (Shautuna: Jurnal Ilmiah Mahasiswa Perbandingan Mazhab, 2026)
Increasing environmental damage shows the limitations of modern environmental law, which still focuses on technical and administrative aspects, while ethical and spiritual dimensions have not been adequately integrated into its normative framework. This condition calls for the strengthening of an ethical-legal foundation that is capable of responding to the environmental crisis in a more holistic manner. This study aims to analyze the concept of Tri Hablum—which includes hablum minallah, hablum minannas, and hablum minal 'alam—as an ethical and normative basis in fiqh bī'ah in order to strengthen the construction of environmental law from an Islamic law perspective. The research problem focuses on the weak ethical-spiritual basis in environmental law regulation and enforcement and the relevance of the Tri Hablum concept as an alternative normative framework. This research is a qualitative literature-based study with a normative and conceptual approach. The research data is sourced from the Qur'an, hadith, fiqh rules, environmental fiqh literature, and relevant laws and regulations, which are analyzed through content analysis and contextual text interpretation techniques. The results of the study show that the Tri Hablum concept forms an integrative and interrelated ethical-legal framework. Hablum minallah places environmental protection as a manifestation of obedience to Allah and human responsibility as caliphs on earth. Hablum minannas emphasizes that environmental damage is directly correlated with social justice and the fulfillment of the collective rights of the community to a good and healthy environment. Meanwhile, hablum minal 'alam views nature as a trust that demands protection, prevention, and sustainable restoration. The novelty of this research lies in the formulation of Tri Hablum as a systemic, integrative, and applicable normative framework of fiqh bī'ah. This research has implications for strengthening the environmental law paradigm so that it is not solely oriented towards administrative compliance, but is also based on moral awareness, social justice, and ecological sustainability.